Dynamics and Innovations within Oomycete Genomes: Insights into Biology, Pathology, and Evolution - Judelson, Howard S. (American Society for Microbiology, 2012)
The eukaryotic microbes known as oomycetes are common inhabitants of terrestrial and aquatic environments and include saprophytes and pathogens. Lifestyles of the pathogens extend from biotrophy to necrotrophy, obligate to facultative pathogenesis, and narrow to broad host ranges on plants or animals. Sequencing of several pathogens has revealed striking variation in genome size and content, a plastic set of genes related to pathogenesis, and adaptations associated with obligate biotrophy. Features of genome evolution include repeat-driven expansions, deletions, gene fusions, and horizontal gene transfer in a landscape organized into gene-dense and gene-sparse sectors and influenced by transposable elements. Gene expression profiles are also highly dynamic throughout oomycete life cycles, with transcriptional polymorphisms as well as differences in protein sequence contributing to variation. The genome projects have set the foundation for functional studies and should spur the sequencing of additional species, including more diverse pathogens and nonpathogens.